Maternal Health in Mozambique: Can Cesarean Section Rates be a Health Indicator in Vulnerable Populations? (Revista Iberoamericana de Bioética, 2021)
This study seeks to reflect on maternal health in Mozambique, its key point being the discussion of whether the rate of Caesarean sections in this population may be used as a health indicator. The rationale for this study is based on the premise that weaknesses in the public health sector in Mozambique lead to increased Caesarean sections in emergency care for vulnerable women, but these Caesarean sections are preventable, as has been disclosed in the media. The analysed material includes the official documents of the Ministry of Health of Mozambique and the World Health Organization. It concludes that there are no arguments for trying to achieve a certain rate of Caesarean sections, rather what is required is prioritising prenatal care all over the country, especially for poorest communities in regions that are far from health centres.
Keywords: cesarean section; health status disparities; prenatal care